A DoS and DDoS Attack Protection System Architecture for the Grid - V. E. Lobanov; B. N. Onykiy; A. A. Stankevichus (Безопасность информационных технологий, 2010)
DoS and DDoS attacks on the Grid are reviewed in the article and a generic architecture and an algorithm are proposed for a protection system to counter these attacks.